Overexpression of DAZL, STRA8, and BOULE Genes and Treatment With BMP4 or Retinoic Acid Modulate the Expression of MSC Overexpressing Germ Cell Genes - Cordero, Paloma; Guerrero-Moncayo, Alejandra; De los Reyes, Monica; Varas-Godoy, Manuel; Cortez, Jahaira; Torres, Cristian G.; Parraguez, Victor H.; Peralta, Oscar A. (Frontiers in Veterinary Science, 2021)
In vitro gamete derivation from stem cells has potential applications in animal reproduction as an alternative method for the dissemination of elite animal genetics, production of transgenic animals, and conservation of endangered species. Mesenchymal stem cells (MSCs) may be suitable candidates for in vitro gamete derivation considering their differentiative capacity and their potential for cell therapy. Due to its relevance in gametogenesis, it has been reported that retinoic acid (RA) and bone morphogenetic protein (BMP) 4 are able to upregulate the expression of specific markers associated to the early stages of germ cell (GCs) differentiation in bovine fetal MSCs (bfMSCs). In the present study, we used polycistronic vectors containing combinations of GC genes DAZL, STRA8, and BOULE followed by exposure to BMP4 or RA to induce GC differentiation of bovine fetal adipose tissue-derived MSC (AT-MSCs). Cells samples at Day 14 were analyzed according to the expression of pluripotent genes NANOG and OCT4 and GC genes DAZL, STRA8, BOULE, PIWI, c-KIT, and FRAGILIS using Q-PCR. Fetal and adult testis and AT-MSCs samples were also analyzed for the expression of DAZL, STRA8, and NANOG using immunofluorescence. Increased gene expression levels in the adult testis and cell-specific distribution of DAZL, STRA8, and NANOG in the fetal testis suggest that these markers are important components of the regulatory network that control the in vivo differentiation of bovine GCs. Overexpression of DAZL and STRA8 in bi-cistronic and DAZL, STRA8, and BOULE in tri-cistronic vectors resulted in the upregulation of OCT4, NANOG, and PIWIL2 in bovine fetal AT-MSCs. While BMP4 repressed NANOG expression, this treatment increased DAZL and c-KIT and activated FRAGILIS expression in bovine fetal AT-MSCs. Treatment with RA for 14 days increased the expression of DAZL and FRAGILIS and maintained the mRNA levels of STRA8 in bovine fetal AT-MSCs transfected with bi-cistronic and tri-cistronic vectors. Moreover, RA treatment repressed the expression of OCT4 and NANOG in these cells. Thus, overexpression of DAZL, STRA8, and BOULE induced the upregulation of the pluripotent markers and PIWIL2 in transfected bovine fetal AT-MSCs. The partial activation of GC gene expression by BMP4 and RA suggests that both factors possess common targets but induce different gene expression effects during GC differentiation in overexpressing bovine fetal AT-MSCs.